UX IN B2B Systems: Specifics of Designing Complex Interfaces for Professional Users - Kondratyuk, Andrii Serhiiovych (Global Prosperity, 2025)
The article focuses on the specifics of UX design in B2B systems, particularly the challenges of designing complex interfaces for professional users. The purpose of the article is to explore the unique characteristics of UX design within B2B systems, with an emphasis on professional usage contexts. The study employed general scientific methods of cognition, such as analysis, synthesis, comparison, systematization, generalization, modeling, and observation. The findings demonstrate that UX design in B2B environments plays a critical role in enabling effective professional interaction. It was found that such UX is tailored to complex, multi-level usage scenarios that reflect the specificity of user roles and the demands of high-load environments. The research showed that the key requirements for B2B system interfaces include aligning information architecture with users’ mental models; integrating functionality with navigation to support continuity of action; and customizing the interface to suit specific user roles. Personalization was shown to significantly reduce cognitive load and enhance overall productivity. Scenario-based modeling enables the creation of logical, consistent user flows that preserve system states and ensure efficient feedback-features that are particularly important for repetitive actions in formalized B2B processes. The study confirmed that UX design directly contributes to reducing task completion time, lowering error rates, and increasing overall system reliability. Usability testing methods that consider the professional use context help identify critical points of frustration and overload. The application of such methods as observation, user action logging, and post-test analysis allows the interface to be adapted to real tasks and workflows. The effectiveness of these techniques is substantiated for the B2B segment, where precision, speed, and interaction reliability are key UX quality indicators. The practical value of the study lies in developing a systematic approach to UX design in B2B systems, which can be applied when creating or improving digital products for professional users.